Early impairment of magnocellular visual pathways mediated by isolated-check visual evoked potentials in primary open-angle glaucoma: a cross-sectional study - Yangfan Yang; Minbin Yu; Zidong Chen; Qiaona Ye; Yanmei Fan; Pingping Liu; Zitian Liu; Kezheng Xu (BMJ Open Ophthalmology)
Objective To explore different performances in the magnocellular (MC) and parvocellular (PC) visual pathways in patients with primary open-angle glaucoma (POAG) and to objectively assess impairment in early stage of POAG.Methods and analysis This is a cross-sectional study. MC and PC visual pathways were assessed using isolated-check visual evoked potential (ic-VEP). Visual acuity, intraocular pressure, fundus examination, optical coherence tomography and visual field were measured. Signal-to-noise ratios (SNRs), mediated by ic-VEP were recorded. The Spearman’s correlation analysis was used to estimate the relationships between visual functions and structures. Receiver-operating-characteristic (ROC) curves were used to estimate the accuracy in detection of early POAG.Results 60 participants (30 early POAG eyes and 30 age-matched control subjects) were recruited. MC visual pathway showed a non-linear response function, while PC visual pathway was a linear response function as contrast increased. Early POAG eyes exhibited significantly weaker initial contrast gains and lower maximum responses in the MC visual pathway (p=0.001, p=0.004, respectively). The SNRs at 8% and 32% depths of modulation (DOM) were significantly correlated with temporal-side retinal nerve fibre layer (RNFL) thickness in early POAG in MC-biased stimulation (p=0.017, p=0.020, respectively). The areas under ROC of 16% DOM were 0.780 (sensitivity 80.0%, specificity 63.3%) with the cut-off SNR of 2.07.Conclusions The MC visual pathway was damaged in the early stage of POAG. The SNRs at 8% and 32% DOM of MC-biased stimulation were significantly correlated with temporal-side RNFL thickness in early POAG, which helped in understanding the mechanisms of visual impairment in the early stage of POAG.